MOTIF MAHASISWA KOTA SURABAYA DALAM MENGGUNAKAN REUSABLE PRODUCT . - Diajeng Sagita Yasmine Wijaya Puteri; Anam Miftakhul Huda (STARKI, 2020)
College students in metropolitan cities like Surabaya are high in the use of disposable products. Consumptive lifestyles, a culture of hanging out, coffee lifestyle, efficiency and low production costs cause companies to produce disposable products. The problem arises of waste and to handle it college students as agents of change do campaign for the use of reusable products. after that eco product company was present andt produced reusable products. By looking at consumer behavior in metropolitan cities and lifestyle in modern society, the company produces reusable products that are current to suit the needs. Such as stainless straw, tumblr, tote bag, cloth mask and other reusable products. Furthermore, the use of reusable products is increasingly being intensified and starting become lifestyle. This research have purpose to find out or determine the motives of colleger in using reusable products with descriptive quantitative methods. With sample of 348 college students from universities and colleges in Surabaya. Questionnaires were distributed with non-probability sampling. Used a Likert scale and analyzed with the mean. Motive variables are divided into four, namely product motifs, patronage motifs, emotional motives and rational motives. From the results of data processing found that college students have different motives in make use of reusable products. It was concluded that the motif with the highest value with 84,8% is the product motif that shows conformity to the needs. Then the patronage motif, means that students have consideration in using it. The third rational motive, the use of reusable products with rational reasons such as to protect the environment, more saving, efficient, and because it is durable. The last emotional motive, shows something that affects individuals using products without rational reasons such as feeling present, cool, influenced by an idol, achieving comfort, because the product is unique and cute, and to achieve pleasure.